2017
DOI: 10.1016/j.redox.2017.04.031
|View full text |Cite
|
Sign up to set email alerts
|

The role of sodium hydrosulfide in attenuating the aging process via PI3K/AKT and CaMKKβ/AMPK pathways

Abstract: Age-related dysfunction of the central auditory system, known as central presbycusis, is characterized by defects in speech perception and sound localization. It is important to determine the pathogenesis of central presbycusis in order to explore a feasible and effective intervention method. Recent work has provided fascinating insight into the beneficial function of H2S on oxidative stress and stress-related disease. In this study, we investigated the pathogenesis of central presbycusis and tried to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 73 publications
2
31
0
Order By: Relevance
“…Accumulating evidence suggests that production of endogenous H 2 S or the administration of exogenous H 2 S can attenuate myocardial injury after ischaemia or reperfusion and decrease BP and resist oxidative stress (X. Chen et al, 2017;L. Li et al, 2008;D.…”
Section: Figurementioning
confidence: 99%
“…Accumulating evidence suggests that production of endogenous H 2 S or the administration of exogenous H 2 S can attenuate myocardial injury after ischaemia or reperfusion and decrease BP and resist oxidative stress (X. Chen et al, 2017;L. Li et al, 2008;D.…”
Section: Figurementioning
confidence: 99%
“…As a gaseous signaling molecule, H 2 S exerts its physiological functions through different manners (Nikolic, Li, Liu, & Wang, ), including modifying proteins (Modis et al, ), affecting ion channels (Papapetropoulos et al, ), influencing metabolism (Sun et al, ), and regulating cell signaling such as Nrf 2 pathway (Calvert et al, ), NF‐κB pathway (De Cicco et al, ), PI3 K/Akt pathway (Chen et al, ) and mTOR pathway (Wang et al, ). It has been well documented that the PI3 K/Akt (De Cicco et al, ; Meng, Yuan, et al, ; Meng, Zhang, et al, ) and mTOR (Jiang et al, ; Li et al, ; Pan, Li, Huang, & Zhang, ) signaling pathway are involved in the regulation of the cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma H2S levels have been reported to decline in an age-dependent manner in human subjects aged 50-80 years, and some studies demonstrated that exogenous H2S contributed to the defense against oxidative damage and mitochondria protection [32]. A recent study reported that exogenous H2S attenuated the aging process via the PI3K/AKT and CaMKKβ/AMPK pathways [33]. In aging cells, damaged mitochondria and proteins accumulate which are toxic to cells and increase ROS production [34].…”
Section: Discussionmentioning
confidence: 99%